Epidemiological Pattern of Injuries in Iran; a Nationwide Review of Seven Million Emergency Department Admissions - Haji Aghajani, Mohammad; Haddadi, Mashyaneh; Saadat, Soheil (Archives of Academic Emergency Medicine, 2017)
Introduction: Globally, it is estimated that around 5.8 million people die annually as result of injuries, which causes 10% of all deaths and 16% of disability adjusted life years lost worldwide. This study aimed to determine the epidemiology of injuries in emergency departments in Iran. Method: This cross sectional study was carried out using national injury surveillance data registry from 21 March 2009 to 20 March 2014. Results: 7,176,344 patients with the mean age of 27.5 ± 17.8 years were registered to 657 EDs (70.6% male). Road Traffic Crash (RTC) was the most common cause of injury (31.0%) followed by hit (28.2%) and fall (10.1%). While roads were the commonest place of injuries, 34.0% of patients have been injured at home. More than 90% of injuries were unintentional. Assault and suicide attempt were causes of injury in 5.6% and 3.9% of patients, respectively. Conclusion: This paper addresses where prevention measures are most urgently needed and offers insights which could be useful for injury prevention programs in Iran and other developing countries.